Kiwinki Syndrome - Abdullayeva Muslima Ahatovna; Eshonkulova Elnora Makhmudovna (Journal of Science in Medicine and Life, 2025)
Kiwinki Syndrome is a rare and relatively under-researched medical condition. It presents a unique set of symptoms that can significantly impact the quality of life of those affected. This article aims to provide a thorough overview of Kiwinki Syndrome, covering its symptoms, causes, diagnosis, and treatment options. Kiwinki Syndrome (KS) is a newly recognized, rare multi-system disorder characterized by a unique constellation of symptoms, including early-onset skeletal dysplasia, progressive neurological deficits, and impaired immune function. This syndrome’s genetic etiology and pathomechanisms remain largely unknown, presenting a significant challenge in diagnosis and treatment.